Emissions of sulfur dioxide and dust at coal power plants of Ukraine - Volchyn, Igor; Haponych, Liudmyla; Bizek, Vladislav (Видавництво Львівської політехніки, 2021)
We developed an algorithm for the estimation of harmful emissions depending on the amount of supplied electricity and heat at coal-fired TPP. By this algorithm, we calculated the emissions of SO2 and dust at Ukrainian TPP in 2017 and 2018. The values of SO2 concentrations in dry flue gases at Ukrainian TPP in 2017 and 2018 depending on fuel brand, sulfur content, and method of slag removal in the boiler were in the range of 1520–5900 mg/Nm3, and the general gross emissions of SO2 were about 620 thousand t. The specific emissions of SO2 were at a level of 14–15 g/kWh of supplied electric energy as compared with 1.2 g/kWh – the level for coal-fired plants of EU countries. At Ukrainian TPP, about 100 thousand t of dust were thrown away. The dust concentrations in flue gases at Ukrainian TPP were equal to 300–1800 mg/Nm3. The values of specific dust emissions per 1 kWh of supplied electricity constituted 0.8–5.1 g against 0.2 g/kWh characteristic of present-day coal-fired TPP of EU countries. The level of gross emissions of SO2 and dust at the TPP of Ukraine did not exceed the maximum possible according to the National Emission Reduction Plan of Pollutants from Large Combustion Plants.
Keywords: thermal power plant; flue gas; harmful emissions; sulfur dioxide; dust; emission limit value